Wafer-level hermetic packaging of 3D microsystems with low-temperature Cu-to-Cu thermo-compression bonding and its reliability - Peng, L. (2013)
Low-temperature wafer-level Cu-to-Cu thermo-compression bonding and its reliability for hermetic sealing application have been investigated in this work. The volume of the encapsulated cavities is about 1.4×10−3 cm3 in accordance with the MIL-STD-883E standard prescribed for microelectronics packaging hermeticity measurement. The samples under test are bonded at 300 °C under a bonding force of 5500 N for 1 h in vacuum (~2.5 × 10−4 mbar) with a 300 nm thick Cu diffusion layer and 50 nm thick Ti barrier layer which are deposited in an e-beam evaporator. The reliability test is accomplished through a temperature cycling test (TCT) from −40 to 125 °C up to 1000 cycles and a humidity test based on IPC/JEDEC J-STD-020 standard. In addition, an immersion in acid/base solution is applied to verify the corrosion resistance of the Cu frame for hermetic application. Excellent helium leak rate which is smaller than the reject limit defined by the MIL-STD-883E standard (method 1014.10) is detected for all the samples. These excellent helium leak rates show an outstanding bonding quality against harsh environment for hermetic encapsulation in 3D integration applications.